Automated street light controlling prototype system with server control - Islam, Tajwarul; Trisha, Sanjida Mazid; Abid, Tanjilur Rahman; Siam, Md. Hasibul Hassan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.